Banks' balance-sheet costs, monetary policy, and the ON RRP - Gara Afonso; Marco Cipriani; Gabriele La Spada (Federal Reserve Bank of New York, 2022)
In June 2022, the Federal Reserve started reducing the size of its balance sheet, which had expanded to just under 9 trillion in response to the COVID-19 pandemic. However, whereas banks' reserves at the Federal Reserve have decreased, the investment of money market funds (MMFs) at the Federal Reserve's overnight reverse repo (ON RRP) facility has continued to increase, reaching 2.4 trillion in September 2022. In this paper, we causally identify the drivers of ON RRP take-up through a diff-in-diff approach. By exploiting a temporary change in the computation of banks' Supplementary Leverage Ratio (SLR) implemented in 2020-21, we show that banks' balance sheet costs incentivize them to push deposits toward MMFs and to reduce their overnight borrowing from MMFs, leading to an increase in MMF investment at the ON RRP. Furthermore, we show that monetary policy tightening, and Treasury bill scarcity are two additional factors contributing to the recent increase in ON RRP usage.
Keywords: G10; G21; E41; E51; E58; 330; balance sheet constraints; banks; leverage ratio; monetary policy; money market funds; ONRRP